2021
DOI: 10.1002/fsn3.2615
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of pomegranate juice addition on physicochemical, microbiological, and functional properties of set and stirred yogurts

Abstract: and Spain are the leading countries in pomegranate production (Farahmand et al., 2017).Annually about 3 million tons of pomegranates are produced in the world, among which Iran is the largest producer with an annual production of 940,000 tons (Troujeni et al., 2018). Pomegranate contains valuable bioactive compounds such as polyphenols, flavonoids, and anthocyanins in its various parts, with functional and medicinal properties, i.e., antioxidant activities, anticancer benefits, and anti-atherosclerotic actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It seems that the main reason for the lower overall acceptance score of the 1% PCP can be attributed to its lower color score. Similarly, Lashkari [31] reported that the cheese samples containing pomegranate juice had higher overall acceptance due to their higher red color.…”
Section: Resultsmentioning
confidence: 97%
“…It seems that the main reason for the lower overall acceptance score of the 1% PCP can be attributed to its lower color score. Similarly, Lashkari [31] reported that the cheese samples containing pomegranate juice had higher overall acceptance due to their higher red color.…”
Section: Resultsmentioning
confidence: 97%
“…Pomegranate juice, a nourishing beverage, is popular due to its sweet and sour taste, which comes from the pomegranate 's simultaneous presence of phenolic chemicals and glucose [19]. The interactions of milk proteins and polyphenols, as well as the development of insoluble, can be used to explain this decrease.…”
Section: Effect Of Pomegranate Juices On Healthmentioning
confidence: 99%
“…The amount of total anthocyanin in yogurt samples with various amounts of pomegranate juice dramatically dropped by 50%-60% after storage. This decline may be linked to anthocyanin degradation, which is most likely caused by the formation of insoluble complexes when anthocyanins and milk proteins interact [19].…”
Section: Effect Of Pomegranate Juices On Healthmentioning
confidence: 99%